1992
DOI: 10.1042/bj2860001
|View full text |Cite
|
Sign up to set email alerts
|

Some ribosome-inactivating proteins depurinate ribosomal RNA at multiple sites

Abstract: Saporin-S6, a ribosome-inactivating protein (RIP) from Saponaria officinalis released more than 1 mol of adenine/mol of ribosomes from house fly (Musca domestica) larvae and from rat liver. The release of adenine from rat liver ribosomes by several RIPs (plant enzymes with RNA N-glycosidase activity) was examined. Saporins, pokeweed antiviral protein from roots of Phytolacca americana (PAP-R), and trichokirin from Trichosanthes kirilowii seeds depurinated rat liver ribosomes at more than one site. Up to 33 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 19 publications
(22 reference statements)
2
44
0
1
Order By: Relevance
“…These effects are catalytic, as shown by molar ratio less than 1 between RIP present in the reaction mixture and adenine released. From the characteristics of their enzymatic activity, RIPs appear to be a non-homogeneous class of enzymes, in that (i) some release one, and some more than one adenine residues per ribosome [14], (ii) some are more active on poly(A) than on RNA [15,16] and (iii) have variable activity on RNA and on DNA (unpublished results). CIP-29 releases only one adenine residue from rat liver ribosomes, is not particularly active on poly(A), but is very active on DNA, more than any RIP assayed so far under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These effects are catalytic, as shown by molar ratio less than 1 between RIP present in the reaction mixture and adenine released. From the characteristics of their enzymatic activity, RIPs appear to be a non-homogeneous class of enzymes, in that (i) some release one, and some more than one adenine residues per ribosome [14], (ii) some are more active on poly(A) than on RNA [15,16] and (iii) have variable activity on RNA and on DNA (unpublished results). CIP-29 releases only one adenine residue from rat liver ribosomes, is not particularly active on poly(A), but is very active on DNA, more than any RIP assayed so far under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 94%
“…RIPs were found to be peculiar N-glycosidases, and to remove a single adenine from a precise position in rRNA (A 4324 in the case of rat liver ribosomes) (review in [13]). More recently, however, it was reported that some, but not all, RIPs remove more than one adenine residue per ribosome [14], and that saporins [15,16] and other RIPs ( [12]; unpublished results by Barbieri et al) remove adenine from RNA other than rRNA and also from DNA. Consistently, ricin removes 2'-deoxyadenine from a synthetic dodecanucleotide with a GdA-GA loop, actually at a faster rate than it removes adenine from a similar dodecanucleotide with a GAGA loop [17].…”
Section: Resultsmentioning
confidence: 99%
“…These RIPs exerts N-glycosidase activity against the 28S RNA of the 60S ribosomal subunit, causing arrest of the protein synthesis which consequently induces cell death (Endo et al 1987, Barbieri et al 1992. RIPs can mainly be divided into 2 groups, type I and type II (Barbieri et al 1993, Nielsen & Boston 2001.…”
Section: Ribosome Inactivating Protein-toxins From Plantsmentioning
confidence: 99%
“…For instance, it has been shown that several RIPs can release adenine from multiple sites in rRNA (5). Furthermore, saporin-L1 can release adenine residues from a variety of nucleic acid substrates, including poly(A), mRNA, tRNA, and DNA (6,7).…”
mentioning
confidence: 99%